The Effectiveness of Group Guidance Based on The Value of Islamic Education in Reducing Academic Procrastination Behavior in Madrasah Aliyah - Sekar Aulia Prameswari; Ira Suryani (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
Academic procrastination is a delay in the academic world. Academic procrastination can have a bad impact on students, so it requires proper treatment for the perpetrators who are called procrastinators. This research wanted to describe the effectiveness of group guidance services based on Islamic education values ​​in reducing academic procrastination behavior in students at MAS Bustaanul Uluum. The research method used is guidance and counseling action research (PTBK) conducted through two cycles of action. The sample selection technique in this study was purposive sampling, so nine (9) students were found to be academic procrastinators. The results of this study were that the pre-cycle students were in the high category of academic procrastination, with an average score of 106.22. In cycle I, there was a change. Namely, students were in the moderate category of academic procrastination, with an average score of 85.7. After the second research cycle, students are in the low category of academic procrastination, with an average score of 63.2. So group guidance services based on Islamic values ​​effectively reduce procrastination behavior in students.